Clustering Design Science Research Based on the Nature of the Designed Artifact - Laine Joakim; Zimmer Markus Philipp; Minkkinen Matti; Salmela Hannu; Mäntymäki Matti (Switzerland, 2022)
During the past two decades, Design Science Research (DSR) has become a central research paradigm in information systems (IS) science. It provides a possibility for researchers to contribute to their field’s existing knowledge base by abstracting knowledge from constructing and using design artifacts. DSR scholars have classified their research paradigm by its potential knowledge contributions looking into dimensions such as researcher role, research activity, and knowledge type. Despite the central role of design artifacts in DSR, we know little about the role of these artifacts for DSR’s knowledge contribution. We therefore extend the discussion on DSR knowledge contributions to the nature of design artifacts, asking how the nature of design artifacts clusters DSR research and its potential knowledge contributions. To answer this research question, we conducted a literature review of DSR research and selected a sample of 20 papers published during the years 2017–2021 in four major IS journals. We found that the nature of the design artifact forms clusters of knowledge contribution and research activity. Our study suggests a relationship between design artifacts, abstractions of knowledge from these artifacts and the conducted research activities. We acknowledge that this relationship stems from a relatively small sample of DSR studies and propose that further research is needed to confirm our findings.
The Role of Digital Technologies in Shaping the Post-Pandemic World: 21st IFIP WG 6.11 Conference on e-Business, e-Services and e-Society, I3E 2022, Newcastle upon Tyne, UK, September 13–14, 2022, Proceedings